TEACHER’S PHYSICAL PRESENCE IN THE CLASSROOM - G’ofurova Maftuna G’ayratjon qizi; Qodirova Nurxon Yusufjon qizi (Ustozlar uchun, 2023)
ABSTRACT: This article explores the significance of a teacher's physical presence in the classroom and its impact on student learning and engagement. The study examines the key aspects of the teacher's physical presence, including proximity, body language, and non-verbal communication. It analyzes the benefits of a teacher's physical presence, such as building rapport, facilitating classroom management, and enhancing instructional delivery. The article also discusses the challenges and considerations associated with physical presence, including the need for adaptability in virtual and hybrid learning environments. By understanding the role and implications of a teacher's physical presence, educators can optimize their instructional strategies and create an inclusive and conducive learning environment.